Fashion and Intellectual Property (Cambridge University Press, 2026)
The book focuses on how fashion designs such as textiles, clothing and footwear, are protected by intellectual property laws which include copyright and trademarks. The authors also discuss a range of topics such as fashion trends, fashion and cultural theories, environmental sustainability and freedom of expression.